Factors that influence consumer purchase decision: case of Petronas Dagangan Berhad / Nor Baizura Mat Yusof - Mat Yusof, Nor Baizura (Faculty of Business and Management, 2009)
The growing competition and the current economic forces require PDB to continuously grow and upgrade its level of service and product to meet the market demand and also to rise above competition. Therefore, it is important for PDB to provide the basic fundamental of marketing strategy in order to meet and satisfy its consumers’ needs and wants. Besides that, PDB needs to understand how consumers of PETRONAS make purchase decision and how marketing strategy influences that decision. This research is about the factors that influence consumer purchase decision. Factors of marketing such as product, price, promotion and place have been identified to investigate whether or not these factors influence the consumer purchase decision. The survey was conducted in three PETRONAS Service Stations (PSS)which are PSS Setiawangsa, PSS Wangsa Maju and PSS Bandar Melaka. The sample size of this study was 30 consumers of PETRONAS products. Data was obtained using primary data. Respondents were required to answer the questionnaires that included the statements of each variable. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpret form. The Statistical Package for the Social Science (SPSS) version 17.0 was used to summarize the data. The results are in form of reliability testing, descriptive statistic, NOVA, T-test and correlation. Based on this research, the result indicates that all the factors except promotion have a moderate relationship with consumer purchase decision. The conclusion of the study is the outcome of the survey analysis and findings. Based on the findings, some recommendations have been suggested in order to improve the understanding on how consumers of PETRONAS make purchase decision and how marketing strategy influences that decision and for future research.